Sharp Szemerédi-Trotter Constructions in the Plane - Guth, Larry; Silier, Olivine (The Electronic journal of combinatorics, 2025)
We present a new family of sharp examples for the Szemerédi-Trotter theorem. These are the first examples not based on a rectangular lattice. We also include an application to the discrete inverse Loomis-Whitney problem.